Retrospective review of the adjunctive use of pre- operative ranibizumab “LUCENTISTM” in the surgical management of diabetic retinopathy in a Tertiary Referral Hospital in Malaysia - Bastion MLC; Siti Aishah S; Aida Zairani MZ; Barkeh HJ (Penerbit UKM, 2010)
A retrospective case series review was conducted to determine the pre-operative role and safety of pre-operative adjunctive anti-vascular endothelial growth factor (anti-VEGF) agent ranibizumab “LUCENTISTM” in patients with diabetic retinopathy requiring vitrectomy. The study involved twenty consecutive eyes of sixteen patients (age range: 46-72 years; mean 57.5 years) which received intravitreal injection of 0.5 - 1 mg of ranibizumab 3 to 8 days (mean 4.4 days) prior to vitrectomy for diabetic retinopathy. There were no local or systemic post-injection complications. Indications for vitrectomy were retinal detachment (RD) [n=11; 3 combined tractional (TRD) - rhegmatogenous RD (RRD), 8 TRD], TRD with vitreous haemorrhage (VH) (n=3) ,VH (n=8) and vitreomacular traction syndrome (n=1). Inclusion criteria include all consecutive eyes of diabetic patients requiring vitrectomy receiving a first pre-operative injection of anti- VEGF. Pre-operative visual acuity (VA) ranged from 6/36 to light perception. All eyes had minimal to moderate intraoperative bleeding. Post-operative VH in eyes without tamponade or gas tamponade was nil (n=1), mild (n=13) or moderate (n=1). Silicone filled eyes had nil (n=1), moderate (n=3) or severe haemorrhages (n=1). Post-operative VA was unchanged (n=2) (10%), improved (n = 14) (70%) or worsened (n=4). VA was 2/60 or better (n=15) to no light perception (n=1). Two eyes achieved 6/12 or better vision (10%). Ten eyes (50%) had 6/36 or better vision. In conclusion, pre-operative intravitreal ranibizumab is safe and useful in diabetic vitrectomy and appears to help with perioperative bleeding leading to improvement in vision.